Birdcatching in Sagada and other poems - Cimatu, Frank (Diliman, Quezon City University of the Philippines Press, 2021)
"Poet-journalist Franklin Cimatu not only wrote a poem about ikik but also used it as a motif for this first collection of poems in English. He caught the poems that flew from the North: poems about his parents, the Marcoses, Cordilleran revolutionaries, Hawaiian sacadas from Candon, and artist-friends from Baguio.

The poems follow his flight path in journalism from the early 1990s up to the 2010s. His subjects are mostly the people he covered. He scoured his old notebooks, newspaper clippings of typhoons, journals of old European explorers and the New York Times on the day he was born. This book is also a very personal collection. Many of these poems are dedicated to his friends and are eulogies to some of them. Add to this the patented play of words and love for the sestina, canzone, and sonnetina.

Some of the poems were part of the collections that won the Palanca Awards and the Procyon Contest for Young Filipinos. Some were published by the Philippines Free Press, Sunday Inquirer magazine, and the Likhaan series."--Back cover.
Baguio-Manila: a Wang-Wei Ticket -- Chainus Movie: Five Slides for Five Friends -- Agua de Mayo: Sestina -- Prewar Postcards -- Century Plant -- Anito -- Ah Beng's Projector -- Troubled Souls: Three from the Cordillera -- Golden Buddha among the Confiscated Marijuana -- The Dogs of Session Road -- Maningning's Flowers -- Painting Frida in the Nude -- Burning Robert -- Apology by Way of Fish -- Birdcatching in Sagada -- Wishes That Were Here: Three Found Poems on the Cordillera -- Ezekiel 25:17 in Bugnay Village -- The Former Ka Sungar of Paracelis -- Odysseus in Manabo -- Like Nijinsky in Fiji -- Marcos Baby: Three Septembers -- Presidential Sestina a.k.a The Blind Date -- Defrosting Ferdie (History of Martial Law in between) -- Bye Borty Bibe Blues -- Pinakbet: A Canzone -- Selling Flowers -- Blue Hawaii Blues: Three Sonnetinas -- Simplicio's Souvenirs -- Secrets -- The Hawaii Five-O's Tsunami Episode -- The Evolution of the Bolo Punch -- The Pacquiao Poems -- Playing Online Chess with My Father Fourteen Years After His Death: Three Sonnets -- The Hunches: Imagining How It Was for the 32 Journalists the Night Before -- Decommissioning Frank -- Requiem: A Birthday Poem -- About the Author.
Keywords: Philippine poetry (English) .